Conflict and order in Svalbard waters - Pedersen, Torbjørn (Universitetet i Tromsø, 2008)
The papers of the thesis are not available in Munin: 1. Pedersen, Torbjørn (2006): «The Svalbard Continental Shelf Controversy: Legal Disputes and Political Rivalries», Ocean Development & International Law, 37 (3-4): 339-358 (publisher's restrictions - Taylor & Francis). Available at http://dx.doi.org/10.1080/00908320600800960 2. Pedersen, Torbjørn & Tore Henriksen: «Svalbard's Maritime Zones: The End of Legal Uncertainty?» (submitted version). Later published: International Journal of Marine and Coastal Law (2009) 24 (1): 141-161. Available at http://dx.doi.org/10.1163/157180808X353920 3. Pedersen, Torbjørn (2008): «The Constrained Politics of the Svalbard Offshore Area», Marine Policy 32 (6): 913-919. (publisher's restrictions - Elsevier). Available at http://dx.doi.org/10.1016/j.marpol.2008.01.006 4. Pedersen, Torbjørn (2008): «The Dynamics of Svalbard Diplomacy», Diplomacy & Statecraft 19 (2): 236-262 (publisher's restrictions - Taylor & Francis). Available at http://dx.doi.org/10.1080/09592290802096299 Appendix: Thesis also included a copy of The Svalbard Treaty, which is available in Lovdata This dissertation examines processes that induce conflict and order in the maritime areas adjacent to the Svalbard archipelago, where Norway’s sovereign rights as coastal state are contested. The first process is the ambiguous causal interplay of international politics and international law: After decades of debate, the parties to it remain reluctant to involve disinterested international third parties to settle their legal differences. Despite the legal character of the dispute, it endures as a political wrangle, as envisaged in a world of Realpolitik . Still, international law is not merely epiphenomenal to politics. International legal rules are cementing Norway’s right to establish and exercise jurisdiction in the zones, hence affecting international politics. The cementing effect of law on international relations goes beyond what was intended at the time of its adoption. The second process, ...